Construction of a ratiometric fluorescence sensing platform based on a DES-CDs/CoOOH/OPD system for ascorbic acid detection. (13th September 2022) - Chang, Peng; Wu, Li-Jun; Yuan, Xu-Can; Wu, Guodong; Bo, Yukun; Yang, Dan; An, Ming; Zhao, Long-Shan
Abstract : Herein, a ratiometric fluorescence sensing platform based on deep eutectic solvent-carbon dots (DES-CDs) was constructed to efficiently determine ascorbic acid (AA). Abstract : Herein, a ratiometric fluorescence sensing platform based on deep eutectic solvent-carbon dots (DES-CDs) was constructed to efficiently determine ascorbic acid (AA). The CDs were synthesized by a hydrothermal method using a green deep eutectic solvent as the carbon source. CoOOH nanosheets (NSs) with oxidative activity were prepared using cobalt chloride as the raw material under ultrasonic conditions. The prepared DES-CDs were combined with CoOOH NSs to construct a fluorescence sensing platform for ascorbic acid (AA) analysis. o -Phenylenediamine (OPD) can be oxidized by CoOOH NSs to 2, 3-diaminophenothiazine (oxOPD) with orange fluorescence. oxOPD can burst the blue fluorescence of DES-CDs through the inner filter effect (IFE). However, the redox reaction between ascorbic acid (AA) and CoOOH NSs can lead to the decomposition of CoOOH NSs, which can attenuate OPD oxidation and reduce the production of oxOPD, further enabling the retention of the fluorescence of DES-CDs. The method was carried out based on the sensing platform constructed using DES-CDs to achieve the detection of AA. Under the optimized conditions, F 450 / F 565 showed good linearity with the concentration of AA in the range of 6.25–200 μM, and the limit of detection (LOD) was 1.81 μM. In addition, the established method was successfully applied to the detection of AA in serum and obtained satisfactory results. This method has the advantages of good selectivity and high accuracy, and has potential applications in the rapid detection of AA.